Softwood Kraft Pulp-Derived Carbon-Supported PtNi Catalysts for the Electrooxidation of Ethanol - Nieva Lobos, María Luz; Sieben, Juan Manuel; Moyano, Elizabeth Laura (Frontiers in Materials, 2020)
In this work, the biocarbons synthesized by fast pyrolysis at 350 °C of raw (BK) and H3PO4 treated (TBK) fibrous fraction of non-bleached softwood kraft pulp has been proposed as novel supports for the deposition of PtNi nanocatalysts. The bimetallic nanoparticles were deposited by pulse microwave-assisted reduction using ethylene glycol both as solvent and reducing agent. The physicochemical properties of the resulting materials were evaluated by means of X-ray diffraction (XRD), transmission electron microscopy (TEM), energy dispersive X-ray microanalysis (EDX) and inductively coupled plasma atomic emission spectroscopy (ICP-AES), whereas the electrochemical activity towards ethanol oxidation in acid medium was evaluated using cyclic voltammetry (CV) and chronoamperometry (CA). Nanosized PtNi particles with average diameters in the range of 2.9-4.1 nm and a nickel content of ca. 30 at. % were deposited over both softwood kraft pulp-derived carbon materials. The electrochemical measurements showed that the bimetallic nanoparticles deposited over the acid-treated biocarbon (PtNi/TBK) exhibit superior catalytic performance in terms of activity, onset potential, and poisoning tolerance. The mass activity of the PtNi nanocatalyst supported over TBK was about 1.3 and 6.3 times higher than that of the bimetallic nanoparticles deposited onto BK and Pt/C, respectively. The effect of the carbonaceous material on the electrocatalytic activity is discussed in detail.